Populations of Dalapon-decomposing Bacteria in Soil as Influenced by Additions of Dalapon or Other Carbon Sources - Burge, Wylie D. (1969)
The numbers of bacteria capable of decomposing the herbicide dalapon were determined for five soils by the most-probable-number method. Before treatment of the soils with dalapon, the numbers varied from 1,000 to 10,000 cells per g of soil. Incubation of the soils with dalapon resulted in large increases (100-fold) in two of three soils in which dalapon was decomposed rapidly. Lack of increase in numbers in spite of rapid decomposition in the other soil probably indicated breakdown by a chemical process or decomposition by fungi. In the remaining two soils, in which decomposition was slow in one and did not occur in the other, the initial numbers were at the low end of the range and the increase was small on incubation with dalapon. Addition of ground alfalfa or ground corn plant material to a soil did not result in significant increases in the numbers of dalapon-decomposing bacteria, either during or after decomposition of the plant material. Glucose depressed the rate of breakdown of dalapon in the soil and increased dalapon-decomposing Bacillus species rather than Arthrobacter and Agrobacterium species, which were found to increase on incubation with dalapon itself. The most-probable-number method appears to be a valuable tool for pesticide-ecology studies.